2020
DOI: 10.22603/ssrr.2019-0089
|View full text |Cite
|
Sign up to set email alerts
|

Novel Titanium Cages for Minimally Invasive Lateral Lumbar Interbody Fusion: First Assessment of Subsidence

Abstract: Author contributions: PRK, BO, GR collected and analyzed patient data including radiographic studies. ACV and PA designed the study and supervised data collection and analysis. All authors contributed in the preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…Importantly, a study by Lim et al showed that subsidence likelihood for a non-porous intervertebral fusion cage was 2.33 times higher in flexion motion than for a porous cage, 1.16 times higher in extension motion, 1.9 times higher in axial rotation motion and 1.81 times higher in lateral bending motion [ 27 ]. Moreover, Krafft et al demonstrated that porous structure led to maximized bone-implant contact area and minimized stress-shielding effect [ 28 ]. Results obtained by Chatham et al proved also that a larger implant-to-bone contact interface provided more even stress distribution, which lowered the risk of subsidence [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, a study by Lim et al showed that subsidence likelihood for a non-porous intervertebral fusion cage was 2.33 times higher in flexion motion than for a porous cage, 1.16 times higher in extension motion, 1.9 times higher in axial rotation motion and 1.81 times higher in lateral bending motion [ 27 ]. Moreover, Krafft et al demonstrated that porous structure led to maximized bone-implant contact area and minimized stress-shielding effect [ 28 ]. Results obtained by Chatham et al proved also that a larger implant-to-bone contact interface provided more even stress distribution, which lowered the risk of subsidence [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Arts et al found that the fusion rate of porous Ti was similar to that of autologous bone–filled PEEK at 12 months during a prospective study of single-segment anterior cervical discectomy and fusion (ACDF) patients using 3D-printed porous Ti neck implants ( Arts et al, 2020 ). Through a clinical comparison, Krafft et al found that the sinking rate of 3D-printed porous Ti interbody fusion cages was significantly lower than that of PEEK interbody fusion cages ( Krafft et al, 2020 ). 3D-printed lamellar Ti cages filled with SiCaP bone grafts can also achieve promising fusion rates in adult degenerative diseases by providing more consistent bone growth and biological fixation ( McGilvray et al, 2018 ; Mokawem et al, 2019 ).…”
Section: Interbody Fusion Cage Materialsmentioning
confidence: 99%
“…Metal 3D printing has facilitated the fabrication of porous cellular scaffolds for orthopedic implants, which have been shown to have the potential to reduce stress shielding and thus reduce bone loss 12–14 . Porous metal implants have also been shown to exhibit excellent osseointegration, 15–17 demonstrated in vivo by porous 3D‐printed titanium interbody fusion cages in animal models 18 and initial patient trials 19,20 . The feasibility of using MRI to monitor bone apposition and implant fixation into the porous coating of a 3D‐printed acetabular shell was also recently demonstrated 21 …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Porous metal implants have also been shown to exhibit excellent osseointegration, [15][16][17] demonstrated in vivo by porous 3D-printed titanium interbody fusion cages in animal models 18 and initial patient trials. 19,20 The feasibility of using MRI to monitor bone apposition and implant fixation into the porous coating of a 3D-printed acetabular shell was also recently demonstrated. 21 An important feature of 3D-printed porous metal structures is their lower density-and hence lower magnetic susceptibility-compared to that of solid metal implants.…”
Section: Introductionmentioning
confidence: 99%